Registration of 'MO 5301D CONV' Soybean. Issue 2 (27th December 2018) - Shannon, G.; Crisel, M.; Smothers, S.; Ali, M. L.; Clubb, M.; Selves, S.; Mitchum, M. G.; Scaboo, A.; Li, Z.; Bond, J.; Meinhardt, C.; Chen, P.
Abstract : 'MO 5301D CONV' [ Glycine max (L.) Merr.] (Reg. No. CV‐528, PI 688604) is a conventional high‐yielding, early maturity group V soybean [ Glycine max (L.) Merr.] cultivar developed at the University of Missouri‐Fisher Delta Research Center and released by the University of Missouri Agricultural Experimentation Station in 2016. MO 5301D CONV is well adapted to Missouri and other southern states. It was developed by conventional breeding from a cross between a high‐yielding line S05‐11482 and a F1 plant of the cross S07‐2680 × LG04‐6000. The F1 plants were grown under lights in the field, and the breeding population was advanced from F2 to F4 generation in Costa Rica using a modified single‐pod descent method. The F4:5 line was selected and bulk harvested for further agronomic evaluation. Before release, MO 5301D CONV was tested with the designation S12‐4718 in 71 environments in Missouri and southern states from 2013 to 2016 for yield and other agronomic traits. MO 5301D CONV yielded higher than the check cultivars in most environments tested. MO 5301D CONV has a relative maturity of 5.3, determinate growth habit, white flower color, light tawny pubescence, and tan pod walls at maturity. The seed has yellow cotyledons with yellow coats and intermediate luster with black hila. MO 5301D CONV performs well across all soil types. It is resistant to stem canker and frogeye leaf spot, is moderately resistant to soybean cyst nematode race 2, peanut root‐knot nematode, and sudden death syndrome, and has field tolerance to Phytophthora root rot. It is also a chloride excluder for tolerance to saline field conditions. Seed of MO 5301D averages 405 g kg −1 protein and 223 g kg −1 oil. The combination of high yield, resistance to diseases, and broad adaptation makes MO 5301D CONV a good cultivar choice for soybean production across US southern states.